2016
DOI: 10.1371/journal.pone.0167992
|View full text |Cite
|
Sign up to set email alerts
|

Distributional Variations in the Quantitative Cortical and Trabecular Bone Radiographic Measurements of Mandible, between Male and Female Populations of Korea, and its Utilization

Abstract: It is important to investigate the irregularities in aging-associated changes in bone, between men and women for bone strength and osteoporosis. The purpose of this study was to characterize the changes and associations of mandibular cortical and trabecular bone measures of men and women based on age and to the evaluation of cortical shape categories, in a large Korean population. Panoramic radiographs of 1047 subjects (603 women and 444 men) aged between 15 to 90 years were used. Mandibular cortical width (MC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 33 publications
4
7
1
Order By: Relevance
“…It is explained by the fact that bone formation rate is high during the mandibular alveolar process. [ 32 ] In agreement with our study, Kavitha et al [ 33 ] suggested that MCW is significantly associated with age and could be considered as a valuable parameter for evaluating the bone strength and osteoporosis regarding postmenopausal women in their study on Korean population. Moreover, Roberts et al[ 34 ] reported that MCW starts to decrease in women and men at ages 42.5 and 36 years, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…It is explained by the fact that bone formation rate is high during the mandibular alveolar process. [ 32 ] In agreement with our study, Kavitha et al [ 33 ] suggested that MCW is significantly associated with age and could be considered as a valuable parameter for evaluating the bone strength and osteoporosis regarding postmenopausal women in their study on Korean population. Moreover, Roberts et al[ 34 ] reported that MCW starts to decrease in women and men at ages 42.5 and 36 years, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…In the present research, the mean FD value was 1.21±0.19 for female and the mean FD value was 1.32±0.08 for male, separately. These results were consistent with the study conducted by Sindaux et al 34 Kavitha et al 35 stated that FD values of males was higher than females at every age and FD decreased with age in both genders. Watanabe et al 36 reported that the FD of male group showed a higher degree of trabecular bone architecture and indicated that the structure of their bone is less prone to osteoporotic fractures.…”
Section: Discussionsupporting
confidence: 92%
“…Most research studies are focused on thresholding-based techniques [7]- [10] for bone segmentation since the higher intensity values of bone are more informative for the separation of bone from the surrounding soft tissue on CT images [11], [12]. However, local thresholding approaches are influenced by intensity in homogeneities [8], [9] and produce poor segmentation results in detecting low-contrast bone contours.…”
Section: Figure 1 Proposed Region-based Segmentation Framework For Fmentioning
confidence: 99%